Analysis of the Importance of Transformational Leadership in Implementing Driving School Program Policies - Nelfi Alida (IAIN Batusangkar, 2022)
This study aims to see how much influence transformational leadership has on the Motivating School Program. Research conducted in the form of library research reveals many things related to transformational leadership and driving school programs, where the driving school program is a form of educational transformation which in its implementation really requires a leader who is open to change, and able to transform the organization and its subordinates to remain relevant to all existing demands. This research is a type of textbook review research which is carried out by collecting literature related to the research topic, then analyzed according to research needs. From the results of the study that the author did, it was found that an important point of educational transformation was the birth of learning with a new paradigm. Learning with this new paradigm will be optimally implemented if the leader in the educational organization is transformational. Because the driving school program is a n